Microscopic structure and thermodynamics of a core-softened model fluid from the second-order integral equations theory - Pizio, O.; Sokołowska, Z.; Sokołowski, S. (Condensed Matter Physics, 2011)
We have studied the structure and thermodynamic properties of isotropic three dimensional core-softened fluid by using the second-order Ornstein-Zernike integral equations completed by the hypernetted chain and Percus-Yevick closures. The radial distribution functions are compared with those from singlet integral equations and with computer simulation data. The limits of the region of density anomaly resulting from different approximate theories are established. The obtained results show that the second-order hypernetted chain approximation can be used to describe both the structure and the density anomaly of this model fluid. Moreover, we present the results of calculations of the bridge functions.